Temperature and Heat Module with Guided Inquiry Model to Improve Student Learning Outcomes - Sultan Syekh Nuhly Rifa Rizkya Robby Hidayatullah; Mastuang Mastuang; Saiyidah Mahtari (Jurnal Ilmiah Pendidikan Fisika, 2026)
The persistently low learning outcomes in physics indicate that students frequently struggle to analyze experimental results in depth—a challenge often exacerbated by conventional teacher-centered instructions. This study developed and evaluated a temperature and heat instructional module integrated with the Guided Inquiry model to enhance student learning outcomes. Employing the ADDIE development framework, the study involved 33 eleventh-grade students at SMA Negeri 1 Angsana as test subjects. Data were gathered using validation instruments, implementation observation sheets, and a learning outcome test, analyzed through quantitative descriptive statistics. The results demonstrated high product validity, with a score of 3.47 and a high reliability coefficient of 0.68. The module exhibited exceptional practicality, achieving a 92% implementation rate. Regarding effectiveness, the module yielded a moderate improvement in learning outcomes, evidenced by an average normalized gain (N-gain) of 0.57. Post-intervention analysis showed that while cognitive scores substantially increased, the formal mastery rate reached 30.3% (10 students), with 69.7% (23 students) still developing proficiency due to persistent algorithmic calculation bottlenecks. It is concluded that the guided inquiry module is valid, highly practical, and moderately effective, serving as a structured pedagogical alternative to bridge conceptual understanding and experimental inquiry in resource-limited physics classrooms.